Tenofovir versus tenofovir plus entecavir for chronic hepatitis B with lamivudine resistance and entecavir resistance. Issue 2 (20th October 2016) - Lee, S.; Ahn, S. H.; Jung, K. S.; Kim, D. Y.; Kim, B. K.; Kim, S. U.; Baatarkhuu, O.; Ku, H. J.; Han, K.; Park, J. Y.
Summary: We compared the viral suppressive efficacy of tenofovir disoproxil fumarate (TDF) mono‐rescue therapy (TDF group) and TDF plus entecavir (ETV) combination‐rescue therapy (TDF + ETV group) in chronic hepatitis B (CHB) patients with lamivudine resistance and entecavir resistance. One hundred and thirty‐three CHB patients with lamivudine and entecavir resistance were investigated. Ninety‐six patients were treated with TDF and 37 with TDF + ETV for at least 6 months. We compared the virologic response rate (HBV DNA level <20 IU/mL) between the two groups and identified the predictive factors of treatment outcome. There were no significant differences between the two groups in demographic characteristics. Up to 24 months [median: 18 (range 6‐24) months], 85.4% and 89.2% of the TDF group and TDF + ETV group, respectively, achieved a virologic response ( P =.068). Only the HBV DNA level at baseline was significantly associated with a virologic response in the multivariate analysis. In a subanalysis of patients with HBV DNA levels ≥4 log (IU/mL) at baseline, a higher proportion of patients in the TDF + ETV group than the TDF group achieved a virologic response (92.9% vs 68.3%; P <.001), while 90% of patients with HBV DNA (IU/mL) levels <4 log in all both TDF and TDF + ETV groups achieved a virologic response. TDF mono‐rescue therapy is a reasonable option in patients with lamivudine resistance and entecavir resistance. However, the combination strategy should be considered in patients with high baseline HBV DNA levels.